Spatially-Resolved Integrated Precipitation-Surface-Groundwater Water Isotope Mapping From Crowd Sourcing: Toward Understanding Water Cycling Across a Post-glacial Landscape - Cole, Alison; Boutt, David F. (Frontiers in Water, 2021)
Isotopic analyses of 18O and 2H of water in the context of the hydrologic cycle have allowed hydrologists to better understand the portioning of water between the different water domains. Isoscapes on a large spatial scale have been created to show isotopic variation in waters as a function of elevation, temperature, distance to coast and water vapor source. We present the spatial and temporal isotopic results of precipitation, surface water, and groundwater of an ongoing study across Massachusetts, USA in order to establish an isotopic baseline for the region. This represents one of the most comprehensive and detailed isotopic studies of water across a 10,000 sq mi area that has exhaustively sampled important components of the terrestrial hydrologic cycle (precipitation, groundwater, and surface waters). The database consists of water samples from 14 precipitation sites, 409 ground water sites and 516 surface water sites across the state of Massachusetts, USA. The results indicate that groundwater isotopic composition ranges from δ18O -11 to -4 ‰ surface water ranges from δ18O -13 to -3.84 ‰ and precipitation ranges from δ18O -17.88 to -2.89 ‰. On a first order, the small bias of mean groundwater (-8.7 ‰) and surface water (-8.0 ‰) isotopes compared to precipitation δ18O (-7.6 ‰) supports that the timing of groundwater recharge and surface water storage effects the isotopic composition surface and groundwater. While differences are distinct, they are larger than previously reported values, but still suggest more importance of summer precipitation than prior acknowledged. Seasonal amplitudes of precipitation (2.7 ‰), surface water (1.13 ‰), and groundwater ( 0 ‰) of the region demonstrate young water fractions of surface water to be 40% with groundwater having no significant annual signal. Results suggest that mean δ18O precipitation, surface water and groundwaters are more enriched in heavy isotopes in areas near the coast, than the interior and western portion of Massachusetts. The hope is for this dataset to become an important tool for water management and water resource assessment across the region.